Feasibility analysis of implementing PV street lighting system in an arid region - Muhaisen, Naser; Khan, Sheroz; Habaebi, Mohamed Hadi; Nabil, Ahmed A.; Ahmed, Musse Mohamud (Taylor & Francis, UK, 2021)
This paper proposes to enhance the execution requirements of the solar photovoltaic (PV) street lighting system in Kuwait. A strength, weakness, opportunity and threat (SWOT) analysis was performed to recognise the elements needed for feasibility analysis followed by analysing the economic and environmental viability. The cost analysis shows that in a year, 18,770,072.56 m3 of natural gas and 4,939,492.779 gallons of fossil fuel can be saved from the installation. Hence, the cost of lowering carbon dioxide (CO2) is directly proportional to the cost of conserved energy resources since emissions from generation stations are reduced by 132,37vc8,406 kg of CO2. The payback period of 3 years and price decrease ratio of 13% shows that this system is economically and environmentally viable.